"Look at Our Country, We Treat Everyone as Equal": College Student Perspectives on Culture. Issue 2 (1st May 2021) - Lee, SuYeon; Parker, Louise; Power, Thomas
Abstract: Only a few studies have investigated how college students who have limited exposure to other cultures (i.e., no traveling experiences, little cross-cultural social interaction) understand and define culture. The current study was intended to capture college students' voices about culture. Three focus groups were conducted with undergraduate college students on issues related to culture. The findings were organized based on the developmental model of intercultural sensitivity. These findings suggest that college students generally lack a deep understanding of their own cultures, as well as other cultures. The findings of this study provide guidance for the development of more effective strategies to increase cultural competency in college students.